Implementasi Raspberry Pi untuk membantu Klinik dan Pengembangan Website Klinik menggunakan Rapid Application Development - Mochammad Haldi Widianto; Della Ihsanti Kusnadi (Politeknik Negeri Cilacap, 2022)
One of the Internet of Things (IoT) components is a microcontroller. One of the many microcontrollers is the Raspberry Pi. This component is often used because it is similar to a small computer. Many people use Rapid Application Development (RAD) in making web-based applications because it is considered very flexible and can iterate on the design and development section. There are several studies related to utilizing website development to help hospitals. However, the real problem is that the use of technology such as clinical information websites has not been widely used for small clinics. This is hampered by the location of the clinics, which are far from the urban center. This study has a goal to develop a website application with the help of a Raspberry Pi. This component works as a computer replacement medium (having wifi and a processor) applied to clinical LED TV because there is no computer to display it, and making the administration of the website itself tested by testing and evaluation using Black Box and User Acceptance Test (UAT). In testing and evaluation, it was found that 5 trials of Black Box testing got good results with all categories achieved. 76.13% of UAT results are included in the